Nostalgia: An impactful social emotion. (February 2023) - Juhl, Jacob; Biskas, Marios
Abstract: Nostalgia (a sentimental longing for one's past) is a highly social emotion. We provide an evidence-based argument that nostalgia's sociality is one of its most defining and impactful characteristics. First, we review evidence that has established the highly social content of nostalgic reflection. Second, we summarize research that has demonstrated nostalgia's capacity to provide a sense of connectedness with others, and that this social connectedness, in turn, conveys intrapersonal psychological benefits (i.e., meaning in life, self-continuity, optimism, inspiration). Third, we outline research that has documented the interpersonal consequences of nostalgia (e.g., greater physical closeness, strengthened relational goals, increased help seeking, intensified empathy, elevated prosocial behavior). Finally, we call for applied research to investigate how the social character of nostalgia can be harnessed to improve people's social lives.